Language law and language rights: perspectives on legal intervention and language diversity - Joseph-G Turi (Acta Academica, 2009)
Language legislation aims to protect or promote the status and use of one or more specified languages. Official language legislation relates to the according of official status to a language or languages, while liberal language legislation pertains to the recognition of language rights and linguistic minorities. Regarding the latter category, a distinction is drawn between the right to the language and the right to a language. The former refers to the right to use one or more specified languages, particularly in an official context, whereas the right to a language refers to the universal right to use one’s mother tongue, or any language, particularly in unofficial contexts. Diversity, including linguistic diversity, is an asset that should be acknowledged and preserved — also in a judicial context.